Identification of Sedimend Algae Species In Intensive Culture of Catfish (Pangasius sp.) in Red Yellow Podsolic Ponds Ages - Roni Mahiwal Pohan; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted from March to May 2017 in the Koto Mesjid village, Kampar district, Riau province and analysis of algae kind in the water quality environment laboratory. The abudance of this research was to defermine of the best of ponds type for differential of ages as a mainteneance ponds. The method of this research used was as experimental method by completely randomized design (CRD) using one factor and 4 levels of (P1= 0-5 years), (P2= 6-10 years ), (P3= 11-15 years) , (P4= 16-20 years ) and 3 repetitions. The result of the research was showed of the 10 spesies were found consisting Cyanophyta, Clorophyta and Xanthophyta (5 spesies, 4 spesies,and 1 spesies) respectively. The best abundance of algae for cuttivation in the P3 (11-15 years) was 11,858 ind / cm2. 1)Student of The Fisheries And Marine Science Faculty, University of Riau2)Lecturer of The Fisheries And Marine Science Faculty, University of Riau Keywords: Sedimend Algae, Intensive culture,Catfish, Pond ages